2014
DOI: 10.3109/02656736.2014.962626
|View full text |Cite
|
Sign up to set email alerts
|

Local thyroid tissue ablation by high-intensity focused ultrasound: Effects on thyroid function and first human feasibility study with hot and cold thyroid nodules

Abstract: HIFU is a safe and effective method to treat benign, solid, complex, hot and cold thyroid nodules preserving thyroid function. Further developments of the system are needed to gain suitability for daily use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
4
33
0
4
Order By: Relevance
“…9,23,27,32 A case report on a single hyperfunctioning nodule demonstrated that 2 weeks after HIFU treatment, the nodule appearance was cystic at US. 33 Thyroid function normalized after 3 months and was maintained during the follow-up to 18 months.…”
Section: Clinical Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…9,23,27,32 A case report on a single hyperfunctioning nodule demonstrated that 2 weeks after HIFU treatment, the nodule appearance was cystic at US. 33 Thyroid function normalized after 3 months and was maintained during the follow-up to 18 months.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…The treatment did not affect thyroid function and no serious immune reaction was observed, despite the significant rise in serum Tg level 1 day after the ablation. 27,35 Patients received either local anesthesia Schematic presentation of all sites intended to treatment; excluded sites are red in color, the sites that will be treated are white in color, and after they receive the pulse, they become green. (C) visualization of hyperechoic mark (white spot) on the point of the treatment cone after the first sonication.…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The percutaneous ethanol injection shows excellent results in cystic nodule volume reduction but poor results in solid nodules [14]. High intensity focused ultrasound is the only non-invasive technique however it works only in small nodules [15]. Benign nodules do not take up enough iodine for radioiodine therapy, so surgery is recommended.…”
Section: Patient's Tolerance and Safetymentioning
confidence: 99%
“…This feasibility study therefore focused on the treatment of benign thyroid nodules, where RFA can offer an alternative to surgery. Alternative treatment options for benign thyroid nodules include percutaneous ethanol injections (PEI) [14], high-intensity focused ultrasound (HIFU) [15] as well as laser, microwave or radiofrequency ablation [2,5,16]. The percutaneous ethanol injection shows excellent results in cystic nodule volume reduction but poor results in solid nodules [14].…”
Section: Patient's Tolerance and Safetymentioning
confidence: 99%